Utilisation of Decision Tables for Proposal of Transfer Node Conception - Martin Jacura; Lukáš Týfa (Promet - Traffic&Transportation, 1970)
The key issue in improving the appeal of public mass transport is the optimal arrangement of transfer nodes. The objective is to propose a comfortable, simple and safe environment for both passengers and operators, and a solution which is economical to construct and operate. Although each transfer node is unique and specific, it is beneficial to have a general idea on the layout of a project to construct or reconstruct such a transfer node. This project should, in particular, stem from the traffic intensity of single transport modes, the volume of single transfer links, and the nature and significance of traffic routes. This article presents the methodology for determining the appropriate disposition of mass public transport nodes using modified decision tables (one of the tools of systems analysis) with specific data particularly applicable in the Czech Republic.